Combined QoS Analysis of Smart Distribution Grids with Constraint Satisfaction Problem and Network Calculus - Alshraa, Abdullah; Vietz, Matthias; Hielscher, Kai-Steffen; Oest, Frauke; Lehnhoff, Sebastian; German, Reinhard (2023 IEEE International Conference on Communications, Control, and Computing Technologies for Smart Grids, SmartGridComm 2023 - Proceedings, 2023)
The expansion of renewable energies requires implementing Smart Grid Services (SGSs) in the distribution grid. Analytical verification of the SGSs' Quality of Service (QoS) requirements is crucial for reliable operation. This paper proposes a two-step approach: a constraint satisfaction problem (CSP) considers network infrastructure and resource allocations to find candidates' solutions. Then, the solutions are evaluated using Network Calculus (NC) to calculate delay bounds at the worst-case and compare them to the requirements. If necessary, alternative solutions are generated. The NC framework is adjustable and considers different service priorities by implementing scheduling policies such as strict priority, weighted fair queuing, weighted round robin, and deficit round robin. In the end, the best-performing parameters are derived for a sample network and the results manifest that the NC framework can be used to analyze random communication networks.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Network Calculus; Quality of Service; Smart Distribution Grid; Smart Grid Services